ChemInform Abstract: Synthesis of Functionalized Pyrazoles via Vanadium‐Catalyzed C—N Dehydrogenative Cross‐Coupling and Fluorescence Switch‐On Sensing of BSA Protein. Issue 12 (March 2016) - Sar, Dinabandhu; Bag, Raghunath; Yashmeen, Afsana; Bag, Subhendu Sekhar; Punniyamurthy, Tharmalingam
Abstract: Alkenyl hydrazones are generated in‐situ from alkenyl ketones and arylhydrazines and give pyrazoles using commercially available, nontoxic, and recyclable VOSO4 as the catalyst and air as the oxidant.